2022
DOI: 10.4102/curationis.v45i1.2261
|View full text |Cite
|
Sign up to set email alerts
|

Technology usage for teaching and learning in nursing education: An integrative review

Abstract: Background: The increasing availability of technology devices or portable digital assistant devices continues to change the teaching-learning landscape, including technology-supported learning. Portable digital assistants and technology usage have become an integral part of teaching and learning nowadays. Cloud computing, which includes YouTube, Google Apps, Dropbox and Twitter, has become the reality of today’s teaching and learning and has noticeably improved higher education, including nursing education.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Digital technology provides opportunities for innovative pedagogy, facilitation of learning and teaching and organization of higher education, including nursing education (Gause et al, 2022). A recent integrative review (Gause et al, 2022) reported that technology is used in clinical and classroom nursing teaching to complement learning, with a recent notable increase in clinical settings. Digital educational resources have supplemented learning in clinical placements and enabled more regular mentoring (Heinonen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Digital technology provides opportunities for innovative pedagogy, facilitation of learning and teaching and organization of higher education, including nursing education (Gause et al, 2022). A recent integrative review (Gause et al, 2022) reported that technology is used in clinical and classroom nursing teaching to complement learning, with a recent notable increase in clinical settings. Digital educational resources have supplemented learning in clinical placements and enabled more regular mentoring (Heinonen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology makes learning fun and interesting and applies to all areas, including nursing education [2]. During the COVID-19 pandemic and social distancing protocols, non-faceto-face education programs, such as online lectures or mobile apps, have increased in number and have been newly developed [3]. Using Metaverse is one of the trends in future education with great potential, especially in the medical area [4].…”
Section: Introductionmentioning
confidence: 99%
“…In nursing education, digital technology is used in the clinic and classroom to supplement learning. However, despite its upward trend, there is still a gap in acceptance [ 18 ]. The use of digital educational technologies is still at an early stage.…”
Section: Introductionmentioning
confidence: 99%